Survival of Escherichia coli 0157:H7 in cultured butter during storage. - GOVARIS (Α. ΓΚΟΒΑΡΗΣ) A.; PAPAGEORGIOU (Δ.Κ. ΠΑΠΑΓΕΩΡΓΙΟΥ) D. K.; PAPATHEODOROU (Κ. ΠΑΠΑΘΕΟΔΩΡΟΥ) K. (Journal of the Hellenic Veterinary Medical Society, 2018)
The survival of E. coli 0157:H7 was examined in 3 types of butter: unsalted, salted with 0.46% and 0.93% salt. The butter samples were inoculated with a low (c.a. 3.14 log CFU/g) or high concentration (c.a. 4.80 log CFU/g) inoculum of the pathogen and were stored at 4°C and 12°C. The contaminated butter samples were stored for 2 months at 4°C and up to visible spoilage (20-26 days) at 12° C. By the end of the storage at 4°C, the tests with the high inoculum of the pathogen revealed that populations of E. coli 0157:H7 were decreased by 2.26 log CFU/g in the unsalted and in 0.46% salted types of butter, and by 2.74 log CFU/g in the 0.93% salted type of butter, while the tests with the low inoculum of the pathogen revealed that populations of E. coli Ol57:H7 decreased by 1.81 log CFU/g in the unsalted type of butter and were detectable in the other types of butter only after enrichment. By the end of the storage at 12°C, the tests with the high inoculum of the pathogen revealed that populations of E coli Ol57:H7 decreased by 2.71 and 3.17 log CFU/g in the unsalted and 0.46% salted types of butter, after 20 and 22 days, respectively and were detectable, in the 0.93% salted type of butter after 26 days, only after enrichment, while the tests with the low inoculum of the pathogen revealed that populations of E. coli O l 57:H7 were decreased by 1.88 log CFU/g in the unsalted type of butter after 20 days, and were detectable, in the 0.46% and 0.93% salted types of butter after 22 and 24 days, respectively, only after enrichment. The initial pH of all butter samples (5.18±0.01) decreased slightly (0.06-0.10) during storage at 4°C, and more (0.48 - 0.54) during storage at 12°C.